SPECIAL STRATEGIES IN AMPUTEE FOOTBALL - Indra Kusuma, Angga; Pieter Pelamonia, Shandy; Rentika Hadi , Shantika; Gede Dharma Utamayasa , I; Kartika Purbowati , Sweeta; Fauzi, Muchlas; Arie Ichtiar, Tiofilus (Antis-publisher, 2025)
Objective: This study aims to identify specific strategies for amputee soccer that consider players' physical limitations while maximizing their potential. Method: The methods applied in this community engagement program include technique training, tactical development, and match simulations. Results: The results demonstrate that implementing specific strategies such as formation adjustments, passing techniques, and team communication significantly enhances the performance of amputee players. Additionally, the program focuses on strengthening players' mental and physical capabilities to support their participation in local and national competitions. Novelty: This initiative highlights the implementation of tailored strategies as a tangible step toward achieving inclusivity in sports. It provides amputee individuals with opportunities to excel, breaking barriers in competitive sports.